2021
DOI: 10.1128/jcm.01316-21
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF Ultra Is Highly Sensitive for the Diagnosis of Tuberculosis Lymphadenitis in a High-HIV Setting

Abstract: Background: Tuberculosis lymphadenitis (TBL) is the most common extrapulmonary TB (EPTB) manifestation. Xpert MTB/RIF Ultra (Ultra) is a World Health Organization-endorsed diagnostic test, but performance data for TBL, including on non-invasive specimens, are limited. Methods: Fine needle aspiration biopsies (FNABs) from outpatients (≥18 years) with presumptive TBL (n=135) underwent: 1) routine Xpert (later Ultra once programmatically available), 2) a M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In contrast to outpatients, where other infections are likely more common (and of higher severity) like in inpatients CRP, will have decreased specificity and may not be as useful yet more data are needed. CRP's potential also requires investigation in extrapulmonary TB, where referral from primary care to a distant facility for invasive sampling (e.g., fine needle aspirate biopsy [ 45 ]) is needed, as well as investigation in HIV-negative patients, where emerging data suggest it may have utility and perform similar to in PLHIV (after threshold adjustment) [ 46 , 47 ].…”
Section: Triage Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to outpatients, where other infections are likely more common (and of higher severity) like in inpatients CRP, will have decreased specificity and may not be as useful yet more data are needed. CRP's potential also requires investigation in extrapulmonary TB, where referral from primary care to a distant facility for invasive sampling (e.g., fine needle aspirate biopsy [ 45 ]) is needed, as well as investigation in HIV-negative patients, where emerging data suggest it may have utility and perform similar to in PLHIV (after threshold adjustment) [ 46 , 47 ].…”
Section: Triage Toolsmentioning
confidence: 99%
“…Users of next-generation tests (some of which are detailed later) should be aware of these lessons learnt from the AlereLAM experience. Finally, Ultra has been applied to urine for both pulmonary and extrapulmonary TB diagnosis; however, yields are generally low [ 45 , 92 ] albeit very ill HIV-positive inpatients are a possible exception [ 93 ].…”
Section: Confirmatory Toolsmentioning
confidence: 99%
“…These findings support the use of Xpert Ultra on FNAs as an initial test when TB adenitis is suspected, as Xpert Ultra has a high sensitivity, is minimally invasive, and gives rapid results ( Antel et al, 2020 ). More recently, Xpert Ultra has proved to be highly sensitive for the diagnosis of TB lymphadenitis in an HIV-endemic setting; this study reported sensitivity and a specificity of 91 and 76%, respectively, for 46 FNA biopsies using a culture and cytology reference standard ( Minnies et al, 2021 ). Several other studies, which, however, analyzed a limited number of lymph node samples, demonstrated a significant diagnostic performance of Xpert Ultra in the detection of M. tuberculosis on lymph node specimens, supporting its use for the diagnosis of TB lymphadenitis, at least as an early test ( Bisognin et al, 2018 ; Piersimoni et al, 2019 ; Hoel et al, 2020 ; Menichini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 78%
“…Despite the lack of concordance between Xpert Ultra and TB-LAM assay, which needs further investigation, the use of Xpert Ultra with urine could represent a rapid and non-invasive test for suspected TB meningitis and a prognostic tool in individuals positive for HIV with TB meningitis ( Cresswell et al, 2020a ). A recent study by Minnies et al assessed the performance of Xpert Ultra on urine samples for the diagnosis of TB lymphadenitis: Xpert Ultra had a low sensitivity (18%) and a high specificity (98%) when tested on urine specimens compared to FNA biopsies; none of the patients negative for HIV had any positive urine Xpert Ultra, while 12% of the patients positive for HIV were urine Xpert Ultra-positive, thus indicating that the use of Xpert Ultra on urine from patients positive for HIV with presumptive TB lymphadenitis could reduce invasive sampling ( Minnies et al, 2021 ). Therefore, urine Xpert Ultra as a tool to diagnose pulmonary or disseminated TB seems to offer good diagnostic usefulness for patients infected with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of Xpert-Ultra was 100% (43/43) using FNA, whereas 96% (55/57) using tissue ( Antel et al , 2020 ). A recent study performed with FNA (n = 92) in a high HIV setting (61% HIV positive cases) showed that Xpert-Ultra had an increased sensitivity (91%) in contrast to Xpert (72%) but demonstrated decreased specificity (76% versus 93%) ( Minnies et al , 2021 ). Until now, no study has been performed to compare Xpert and Xpert-Ultra's performances in diagnosing TB lymphadenitis from low HIV settings, which might have different patient characteristics from the patients in high HIV burden countries.…”
Section: Introductionmentioning
confidence: 99%